Sustained Shugoshin 1 downregulation reduces tumor growth and metastasis in a mouse xenograft tumor model of triple-negative breast cancer - Shirley Jusino; Yainyrette Rivera-Rivera; Camille Chardón-Colón; Patricia C. Rodríguez-Rodríguez; Janeishly Román-González; Valeria S. Juliá-Hernández; Angel Isidro; Qianxing Mo; Harold I. Saavedra (Cell Division, 2023)
Abstract Background Triple-negative breast cancer (TBNC) is an aggressive breast cancer subtype with a poor prognosis. Shugoshin-1 (SGO1) protects chromatids from early separation. Previous studies from our group have demonstrated that transient SGO1 downregulation suppresses early stages of metastasis (the epithelial-to-mesenchymal transition, or EMT, cell invasion, and cell migration) in TNBC cells. Thus, the inhibition of SGO1 activity may represent a potential therapeutic intervention against cancers that progress to metastasis. Therefore, we aimed to investigate the effects of sustained shRNA-mediated SGO1 downregulation on tumor growth and metastasis in TBNC. To that end, female NOD-SCID Gamma (NSG) mice were injected with 2.5 × 106 shRNA Control (n = 10) or shRNA SGO1 (n = 10) MDA-MB-231 cells. After eight weeks, the number of mice with metastasis to the lymph nodes was calculated. Primary and metastatic tumors, as well as lung and liver tissue, were harvested, measured, sectioned, and stained with hematoxylin and eosin (H&E) stain. Results Tumor growth and metastasis to the lymph nodes and lungs were significantly reduced in the shRNA SGO1-treated mice group, while metastasis to the liver tends to be lower in cells with downregulated SGO1, but it did not reach statistical significance. Furthermore, sustained SGO1 downregulation significantly reduced cell proliferation, cell migration, and invasion which correlated with lower levels of Snail, Slug, MMP2, MMP3, and MMP9. Conclusion The supression of SGO1 activity in TNBC harboring dysregulated expression of SGO1 may be a potential target for preventing breast cancer growth and metastasis.